2018
DOI: 10.1111/jocn.14313
|View full text |Cite
|
Sign up to set email alerts
|

How fundamental aspects of nursing care are defined in the literature: A scoping review

Abstract: This scoping review identified areas of convergence and divergence around fundamental aspects of nursing care. An agreed definition for such care is needed to enable the development of a robust evidence base to underpin the coherent and consistent development of nursing practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
83
0
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(97 citation statements)
references
References 45 publications
2
83
0
7
Order By: Relevance
“…Nurses have reported to take CFs into consideration on average from “enough” to “much,” specifically with regard to (in order) verbal and non‐verbal communication, patient‐centred approach, psychical contact and empathetic therapeutic alliance, which all represent core concepts of caring (Feo, Kitson, & Conroy, ; Pettersson et al, ). An inferior degree of trust has been reported, in order, in professional reputation, uniform, adequate environment and design, which represent factors capable of increasing care humanisation as emphasised in the recent literature (Heras La Calle, Ovies, & Tello, ), thus not included yet in undergraduate and continuing education programmes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nurses have reported to take CFs into consideration on average from “enough” to “much,” specifically with regard to (in order) verbal and non‐verbal communication, patient‐centred approach, psychical contact and empathetic therapeutic alliance, which all represent core concepts of caring (Feo, Kitson, & Conroy, ; Pettersson et al, ). An inferior degree of trust has been reported, in order, in professional reputation, uniform, adequate environment and design, which represent factors capable of increasing care humanisation as emphasised in the recent literature (Heras La Calle, Ovies, & Tello, ), thus not included yet in undergraduate and continuing education programmes.…”
Section: Discussionmentioning
confidence: 99%
“…Nurses have reported to take CFs into consideration on average from "enough" to "much," specifically with regard to (in order) verbal and non-verbal communication, patient-centred approach, psychical contact and empathetic therapeutic alliance, which all represent core concepts of caring (Feo, Kitson, & Conroy, 2018;Pettersson et al, 2018 "unaware" were removed from the analysis; moreover, the five levels of Likert scale were collapsed into three categories (Likert 0, "never" + Likert 1, "at least once per year" = "never"; Likert 3, "at least once per week" + Likert 4, "daily" = "very often"), leaving therefore unaltered the central categories (Likert 2, as "occasionally"). and environment (Sherman & Hickner, 2008) represent important CFs and milestones of personal branding as an "introspective process by which you define yourself professionally" capable of influencing clinical outcomes and to increase professional development and reputation (Philbrick & Cleveland, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Kitson et al identified 14 aspects of fundamental care and these have formed the basis of a body of work around refining and further conceptualization into a framework and point‐of‐care nursing theory (Kitson, ). Feo et al () in a scoping review explored the main ways the fundamentals of care are defined in the literature. They point to a dichotomy between the fundamentals of care conceptualized as a list of nursing activities or alternatively as a “complex, multidimensional construct that emphasizes nursing tasks; the need to develop trusting, positive relationships with patients; and the care context” (Feo et al, , p. 2,225).…”
Section: Discussionmentioning
confidence: 99%
“…Feo et al () in a scoping review explored the main ways the fundamentals of care are defined in the literature. They point to a dichotomy between the fundamentals of care conceptualized as a list of nursing activities or alternatively as a “complex, multidimensional construct that emphasizes nursing tasks; the need to develop trusting, positive relationships with patients; and the care context” (Feo et al, , p. 2,225). Feo et al () further distinguished between fundamentals of care and compassionate care with the latter having greater emphasis on values, attitudes and behaviours of nurses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation